2005
DOI: 10.1128/jcm.43.5.2375-2379.2005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cyclospora cayetanensis Oocysts in Human Fecal Specimens by Flow Cytometry

Abstract: A diagnosis of cyclosporiasis typically involves stool examinations for the presence of Cyclospora oocysts by means of microscopy. In recent years, flow cytometry has been gaining in popularity as a novel method of detecting pathogens in environmental and clinical samples. The present study is an evaluation of a flow cytometric method for the detection and enumeration of Cyclospora oocysts in human fecal specimens associated with food-borne outbreaks of cyclosporiasis in Ontario, Canada. Flow cytometry results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 16 publications
0
28
0
7
Order By: Relevance
“…This characteristic has been used to confirm the diagnosis of Cyclospora and also to purify the parasite from human fecal samples by flow cytometry. Detection of fluorescence has also been suggested as a useful alternative for screening large numbers of samples in the event of an outbreak (56).…”
Section: Diagnosismentioning
confidence: 99%
“…This characteristic has been used to confirm the diagnosis of Cyclospora and also to purify the parasite from human fecal samples by flow cytometry. Detection of fluorescence has also been suggested as a useful alternative for screening large numbers of samples in the event of an outbreak (56).…”
Section: Diagnosismentioning
confidence: 99%
“…cysts in fecal samples (Dixon, 1997;Dixon, 2002;Ferrari, 2003), in detection of Cryptosporidium in SCID mice (Arrowood, 1995), seeded horse feces (Cole, 1999), and seeded human stool specimens (Valdez, 1997). In addition to detection and enumeration, large-scale sorting could also be used in conjunction with flow cytometry to yield partially purified oocysts for research purposes, such as food-spiking and recovery experiments, viability determination, or molecular characterization (Dixon, 2005).…”
Section: Jacobbergermentioning
confidence: 99%
“…Dixon et al (2005) involves an evaluation of the effectiveness of flow cytometry for the detection and enumeration of Cyclospora cayetanensis oocysts in human fecal specimens. Using flow cytometry, oocysts could be separated according to their autofluorescence, size, and complexity, and a cluster representing Cyclospora oocysts could be clearly observed on the dot plots of positive samples (autofluorescence vs SSC, with gate region R1 for Cyclospora oocysts).…”
Section: Ferrari Et Al (2003) Proposed An Analysis For Detection Of mentioning
confidence: 99%
“…Flow cytometry (FC) has been reported to be a rapid and sensitive method for screening large numbers of fecal samples for the presence of protozoan cysts and oocysts. 5,6 While FC may not be considered confirmatory in itself, samples found to be positive or equivocal by FC can be readily examined and confirmed by IM. In addition, cell sorting of FC-positive samples can be used to further concentrate the cysts prior to microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of earlier studies, FC has been found to be a rapid and sensitive screening tool for detecting the presence of a variety of protozoan parasites in fecal samples from humans and animals. 2,[4][5][6]14,18,23 Results from the present study suggest that with optimization, FC could be useful in surveillance and prevalence studies involving bovine fecal samples in which a large number of samples may preclude the use of more time-consuming microscopic methods. It should be reiterated, however, that FC is meant to be used only as a screening tool and that any FC positive samples should be confirmed wherever possible using microscopy.…”
mentioning
confidence: 99%